PREPARATION OF ABHRAK BHASMA AND ITS EVALUATION ON MODERN PARAMETERS - Hareshwar, *Sule; Mayuri, Dani; Raman, Belge (International Journal of Ayurveda and Pharma Research, 2017)
Bhasma is an ash obtained through incineration; raw material are processed for purification and this process involves incorporation of some other minerals and/or herbal extract which leads to various reactions in processed material. Bhasma are important in maintaining optimum alkalinity for good health, neutralizing harmful acids that lead to illness; because Bhasma do not get metabolized so they don’t produce any harmful metabolite, rather it breakdowns heavy metals in the body. In todays era, standardization is utmost necessary to confirm its identity and to determine its quality, purity, safety, effectiveness and acceptability of the product. But the most important challenges faced by Ayurvedic formulations are the lack of complete standardization by physiochemical parameters. Abhrak Bhasma having various therapeutic uses has been used since long in Ayurveda. Present study deals with pharmaceutical procedures like Shodhan, Dhanyaabhrak Nirman, Maran of Abhrak. To assure the quality of Bhasma, Rasa shastra quality control tests like Nischandratva, Varitaratwa, Rekhapurnatva, etc., were used then the Bhasma was analyzed using modern parameters like LOD, LOI, Estimation of Iron, Aluminium, Magnesium, silica, XRD and SEM analysis. XRD study of Abhrak bhasma shows various peaks which shows presence of Mica, FeSO4, Fe2O3 in it. SEM study shows the presence of nanoparticles in which particle size ranges from 1 to 200 micron which is an invention of this new era.